2007
DOI: 10.1016/j.actbio.2006.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Influence of thrombin concentration on the mechanical and morphological properties of cell-seeded fibrin hydrogels

Abstract: Fibrin is a biopolymer that has been used in a variety of biomaterial, cell delivery and tissue engineering applications. The enzyme thrombin catalyzes the formation of fibrin microfibrils, which form a three-dimensional mesh in which cells can be directly embedded at the time of gel formation. In this study, fibrin hydrogels containing vascular smooth muscle cells were created using varying concentrations of thrombin. Over 7 days in culture, all gels decreased in volume as the fibrin matrix compacted, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
144
3
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(156 citation statements)
references
References 28 publications
8
144
3
1
Order By: Relevance
“…4b-d). Overall, the results obtained in this study are consistent with those reported in literature [20,23,57,58]. For the same enzyme ratios (LL, HL, LH, HH), higher fibrinogen concentrations consistently gave higher G' values.…”
supporting
confidence: 83%
See 1 more Smart Citation
“…4b-d). Overall, the results obtained in this study are consistent with those reported in literature [20,23,57,58]. For the same enzyme ratios (LL, HL, LH, HH), higher fibrinogen concentrations consistently gave higher G' values.…”
supporting
confidence: 83%
“…For the same enzyme ratios (LL, HL, LH, HH), higher fibrinogen concentrations consistently gave higher G' values. The effect of thrombin is not clear as contradictory findings have been reported in the literature; while a higher thrombin concentration decreased the material modulus in tensile tests of fibrin matrices encapsulating cells [58], a similar effect was only seen for higher thrombin to fibrinogen ratios (0.08 U/mg fibrinogen) in another study, with lower ratios having the opposite effect [20]. For the LH and HH compositions a different trend with thrombin concentration is seen for 5 and 20 mg/mL fibrinogen.…”
mentioning
confidence: 42%
“…L‐PRF contains a dense fibrin fibre network where platelets and leucocytes are enmeshed and it can serve as scaffold for other type of cells due to its favourable mechanical properties (Rowe et al. 2007, Khorshidi et al. 2016).…”
mentioning
confidence: 99%
“…The physical properties of fibrin can be controlled in many ways. For example, the fibrinogen concentration, fibrinogen to thrombin ratio, Ca 2+ concentration, addition/ absence of Factor XIII, and pH conditions strongly regulate the network density of the fibrin gel [10]. However, fibrin gels undergo degradation and strong matrix remodeling in vitro, which results in construct shrinkage and weight loss [11].…”
Section: Introductionmentioning
confidence: 99%